Intranasal Leptin Prevents Opioid-induced Sleep-disordered Breathing in Obese Mice - Freire, Carla (Am J Respir Cell Mol Biol, 2020)
Respiratory depression is the main cause of morbidity and mortality associated with opioids. Obesity increases opioid-related mortality, which is mostly related to comorbid obstructive sleep apnea. Naloxone, a μ-opioid receptor blocker, is an effective antidote, but it reverses analgesia. Like humans with obesity, mice with diet-induced obesity hypoventilate during sleep and develop obstructive sleep apnea, which can be treated with intranasal leptin. We hypothesized that intranasal leptin reverses opioid-induced sleep-disordered breathing in obese mice without decreasing analgesia. To test this hypothesis, mice with diet-induced obesity were treated with morphine at 10 mg/kg subcutaneously and with leptin or placebo intranasally. Sleep and breathing were recorded by barometric plethysmography, and pain sensitivity was measured by the tail-flick test. Excitatory postsynaptic currents were recorded in vitro from hypoglossal motor neurons after the application of the μ-opioid receptor agonist [D-Ala(2), N-MePhe(4), Gly-ol]-enkephalin and leptin. Morphine dramatically increased the frequency of apneas and greatly increased the severity of hypoventilation and obstructive sleep apnea. Leptin decreased the frequency of apneas, improved obstructive sleep apnea, and completely reversed hypoventilation, whereas morphine analgesia was enhanced. Our in vitro studies demonstrated that [D-Ala(2), N-MePhe(4), Gly-ol]-enkephalin reduced the frequency of excitatory postsynaptic currents in hypoglossal motoneurons and that application of leptin restored excitatory synaptic neurotransmission. Our findings suggest that intranasal leptin may prevent opioid respiratory depression during sleep in patients with obesity receiving opioids without reducing analgesia.